Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3892/or.2018.6631
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen enhances tumor growth and angiogenesis indirectly via mediation of bone marrow‑derived cells as well as directly through stimulation of tumor and endothelial cells

Abstract: Estradiol (E2) is a prime culprit for enhancing the progression of female hormone‑related cancers. Bone marrow‑derived cells (BMDCs) have been found to play a pivotal role in tumor growth. Estrogen receptors (ERs) are also found on certain subtypes of BMDCs, in addition to endothelial cells (ECs) and certain tumor cells. However, the role of BMDCs in E2‑induced tumor biology is still unclear. Thus, the effects of E2 on ER‑negative 4T1 breast cancer growth, the mobilization and recruitment of BMDCs, and interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Previous studies have confirmed that 17β-estradiol (E2) can participate in hormone-dependent tumor proliferation and metastasis through a variety of mechanisms [ 39 , 40 ]. The biological role of E2, in addition to directly binding to ER to mediate genomic effects, can also rapidly induce extracellular signal-regulated kinase 1/2 (ERK1/2) phosphorylation to trigger intracellular non-genomic effect [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have confirmed that 17β-estradiol (E2) can participate in hormone-dependent tumor proliferation and metastasis through a variety of mechanisms [ 39 , 40 ]. The biological role of E2, in addition to directly binding to ER to mediate genomic effects, can also rapidly induce extracellular signal-regulated kinase 1/2 (ERK1/2) phosphorylation to trigger intracellular non-genomic effect [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The substantial majority of studies showing the effect of E2 on cancer cell proliferation ( 45 , 46 ), survival, angiogenesis ( 47 ), migration, invasion ( 48 ) or metastasis ( 17 ) have been performed in bi-dimensional cell cultures. Although bi-dimensional models have been helpful for understanding the biochemistry and physiology of cancer cells, such information has been difficult to translate into treatment and early detection or biomarker identification of actual tumors, because bi-dimensional cultures does not reflect the physiological behavior of tumor cells in situ .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no other previous clinical study has identified female sex as a risk factor for tumour growth. However, as in other tumours, oestradiol enhances the progression and migration of endothelial cells in adrenal tumours [ 26 ]. In fact, the proliferation rate in steroidogenic cells of female rats is 6.3-fold higher than in male rats [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%